2009
DOI: 10.1097/nna.0b013e318195a82b
|View full text |Cite
|
Sign up to set email alerts
|

Creating a Positive Work Environment

Abstract: The nursing shortage is negatively affecting the quality, effectiveness, and timeliness of patient care, which warrants a transformation of the nursing work environment. The Nurse-Friendly (NF) Hospital Project assisted 30 rural or small hospitals implement 12 NF criteria into hospital policies to create a positive work environment. The NF criteria represent organizational attributes necessary for ensuring quality patient care, positive work environment, professional development, and nurse satisfaction. The au… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 6 publications
1
13
0
1
Order By: Relevance
“…However, they are very similar, as far as the proportion of men and women (1 man for every 6 women) and the mean age of the nurses surveyed (over 40 years) is concerned. Regarding the professional experience (mean = 20.9 years) our study obtains similar figures to those achieved by [Gerrish et al (2011) 43]in England , but, on the whole, they are higher than those in other similar studies carried out in the United States, where the mean number of years worked is 10 [42,44]. With respect to the academic level it is difficult to compare with other countries like the United Kingdom, United States or Canada, where most of the studies have been conducted and nurses have a long tradition in professional development, including the possibility of access to a doctorate.…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…However, they are very similar, as far as the proportion of men and women (1 man for every 6 women) and the mean age of the nurses surveyed (over 40 years) is concerned. Regarding the professional experience (mean = 20.9 years) our study obtains similar figures to those achieved by [Gerrish et al (2011) 43]in England , but, on the whole, they are higher than those in other similar studies carried out in the United States, where the mean number of years worked is 10 [42,44]. With respect to the academic level it is difficult to compare with other countries like the United Kingdom, United States or Canada, where most of the studies have been conducted and nurses have a long tradition in professional development, including the possibility of access to a doctorate.…”
Section: Discussionsupporting
confidence: 85%
“…The ratio of nurses per population in Spain is below the European standard [57]. It is well known that a shortage of nurses creates a loop of job dissatisfaction due to work overload, which results in a worse quality of care provided and it is an important barrier for implementing EBCP [44,54]. In studies conducted in the Spanish PHC environment, the need for training and adequacy of staff dimension is highlighted, emphasizing the imbalance between nursing staff and GPs, with poorer figures in nurses.…”
Section: Discussionmentioning
confidence: 99%
“…Nurse work environment was measured by eight studies (N = 8, 57.14%) as a holistic concept consisting the dimensions of support received by nurses, competence, relationships, leadership, and autonomy (Aiken, Buchan, Ball, & Rafferty, 2008;Aitken et al, 2011;Calarco, 2011;Gardner et al, 2009;Hall et al, 2008;Jeon et al, 2018;Meraviglia et al, 2009;Van Bogaert et al, 2017). Two studies using participatory approach showed outcome improvement.…”
Section: Nurse Work Environmentmentioning
confidence: 99%
“…However, the basic principle of involving all staff in the improvement of the working culture is reinforced. These two approaches [78,79] have some similarities to the Magnet Hospital approach [80] which has been subject to extensive research [81][82][83][84][85][86][87] which has demonstrated the importance of having appropriate systems and procedures in place to support staff if high standards of patient care are to be delivered. This point is echoed in two review papers [88,89] which conclude that if organisations care for staff they are more likely to be loyal and productive [88] and nurses should feel they are supported, respected and know their contribution is valued, and that they have what they need to care for their patients.…”
Section: Published By Sciedu Pressmentioning
confidence: 99%
“…Meraviglia et al [78] worked with the Texas Nurses Association to devise 12 Nurse Friendly Hospital Criteria which were then introduced into 30 rural hospitals. The criteria included items such as control of nursing practice, safety of the work environment, nurse recognition, zero tolerance of nurse abuse, and middle management accountability.…”
Section: Organisation Wide Interventionsmentioning
confidence: 99%